POLA KOMUNIKASI INTERPERSONAL GURU DENGAN ANAK AUTIS DALAM PEMBELAJARAN DI SD SURYO BIMO KRESNO - Salsabila Besta Kirana; Septianingtyas; Muhammad Dzaki Athallah Hanan; Zulfa Fahmy; Irma Masfia (CV. Adiba Aisha Amira, 2024)
Communication plays a vital role in life, without it, humans can’t understand one another. Communication is also needed between teachers and their students, however not all students are typical, some have disabilities, such as autism, requiring special attention. To address this issue, appropriate educational institutions are needed to handle autistic children and pay attention to their communication methods. One such institution is inclusive schools. The aim of this research is to understand the patterns of interpersonal communication between teachers and autistic children during learning in inclusive school, as well as the effort made by teachers to overcome communication challenges when communicating with autistic children. The research method used in this study is qualitative, employing a qualitative descriptive approach through a case study design.. Data collection techniques include observation of verbal and nonverbal behaviors of autistic children and interviews with classroom teachers. The results show that when communicating with teachers, autistic children tend to use verbal communication. Effective efforts made by teachers to overcome communication challenges include a personal approach to understanding individual needs.